PMSE strength during enhanced D region electron densities: Faraday rotation and absorption effects at VHF frequencies - Chau, Jorge L.; Röttger, Jürgen; Rapp, Markus (Journal of Atmospheric and Solar-Terrestrial Physics, 2014)
In this paper we study the effects of absorption and Faraday rotation on measurements of polar mesosphere summer echoes (PMSE). We found that such effects can produce significant reduction of signal-to-noise ratio (SNR) when the D region electron densities (Ne) are enhanced, and VHF radar systems with linearly polarized antennas are used. In particular we study the expected effects during the strong solar proton event (SPE) of July 2000, also known as the Bastille day flare event. During this event, a strong anti-correlation between the PMSE SNR and the D-region Ne was found over three VHF radar sites at high latitudes: Andøya, Kiruna, and Svalbard. This anti-correlation has been explained (a) in terms of transport effects due to strong electric fields associated to the SPE and (b) due to a limited amount of aerosol particles as compared to the amount of D-region electrons. Our calculations using the Ne profiles used by previous researchers explain most, if not all, of the observed SNR reduction in both time (around the SPE peak) and altitude. This systematic effect, particularly the Faraday rotation, should be recognized and tested, and possibly avoided (e.g., using circular polarization), in future observations during the incoming solar maximum period, to contribute to the understanding of PMSE during enhanced D region Ne.